Se positionner comme chercheuses au prisme des luttes intersectionnelles : décentrer la notion d’allié.e pour prendre en compte les personnes concernées - Sklaerenn Le Gallo; Mélanie Millette (Genre, Sexualité et Société)
This paper aims to problematize and reframe the notion of allyship within social struggles. We proceed in three stages in order to think about the positioning of allies. Based on the standpoint theory of the question of speaking for / speaking of, we take a critical look at the power relationships within academia, and particularly the practices of speech capture by researchers in a privileged position, in the context of research with LGBTQI+ people, racialized, or people marginalized by different streams of oppression. We will then problematize the concept of the allied individual, with particular attention to the ways in which the American academic literature treats the ally/allied individual as an identity to be developed. Finally, we will mobilize the recommendations made by people situated in relation to a particular oppression, within the academic world, but also by relaying the voices of the community members themselves. Facilitating the agency of the people concerned enables an original, more equitable framework to emerge, where participants have the power to recognize or refuse the status of an ally, based on their objectives and needs.